The Effect of Board Gender Diversity on the Company: A Literature Review - Kadek Agus Darmawan (Journal La Sociale, 2024)
This study explores the influence of gender diversity in boards of directors on various aspects of corporate performance. Through the literature review method, this research gathers empirical evidence to assess how gender diversity affects risk-taking, social responsibility, and decision-making processes within the firm. The results show that the presence of women on boards can contribute positively to corporate performance, innovation, investment, and ESG issues, while bringing diverse perspectives, experiences, and expertise that support more effective decision-making and risk management. On the other hand, the study also recognizes that underrepresentation of women may reduce the benefits of gender diversity. Furthermore, the presence of women on boards is associated with reduced agency problems, increased dividend payouts and more responsible tax avoidance practices. However, there are mixed views regarding the impact of gender diversity, emphasizing the importance of considering the firm-specific context in evaluating the impact of gender diversity on firm performance. This study contributes to future research by providing a broader and deeper knowledge base on the topic of gender diversity in the context of business and management.